2011
DOI: 10.1016/j.poly.2010.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Integrated X-ray crystallography, optical and computational methods in studies of structure and luminescence of new synthesized complexes of lanthanides with ligands derived from 2,6-diformylpyridine

Abstract: The reaction of 2,6-diformylpyridine-bis(benzoylhydrazone) [dfpbbh] and 2,6-diformylpyridine-bis (4-phenylsemicarbazone) [dfpbpsc] with lanthanides salts yielded the new chelates complexes [Eu(dfpbpsc-H +) 2 ]NO 3 (1), [Dy(fbhmp) 2 ][Dy(dfpbbh-2H +) 2 ]Á2EtOHÁ2H 2 O (fbhmp = 2-formylbenzoylhydrazone-6-methoxide-pyridine; Ph = phenyl; Py = pyridine; Et = ethyl) and [Er 2 (dfpbbh-2H +) 2 (l-NO 3) (H 2 O) 2 (OH)]ÁH 2 O. X-ray diffraction analysis was employed for the structural characterization of the three chela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…For this purpose, we have chosen [Er­(OH) n ] m ∓ models where the Er–O distances are kept at 2.3 Å, the O–H bond distances are fixed at 1 Å, and the Er–O–H bond angle(s) are fixed at 180° to preserve the symmetry for all of the models. We would like to note here that the models considered here are fictitious and are employed here only to probe the role of symmetry and coordination number; however, the linear coordination tested here might be achievable with ligands such as cyanides . Models studied here are shown in Figure , along with the computed g zz anisotropy axis and the energies of low-lying eight KDs for model complexes from C.N.1 to C.N.12 are provided in the Supporting Information (see Table S16).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, we have chosen [Er­(OH) n ] m ∓ models where the Er–O distances are kept at 2.3 Å, the O–H bond distances are fixed at 1 Å, and the Er–O–H bond angle(s) are fixed at 180° to preserve the symmetry for all of the models. We would like to note here that the models considered here are fictitious and are employed here only to probe the role of symmetry and coordination number; however, the linear coordination tested here might be achievable with ligands such as cyanides . Models studied here are shown in Figure , along with the computed g zz anisotropy axis and the energies of low-lying eight KDs for model complexes from C.N.1 to C.N.12 are provided in the Supporting Information (see Table S16).…”
Section: Resultsmentioning
confidence: 99%
“…The rest of the emission bands were small compared with the latter. It has been previously reported that these characteristics are indicative of low-symmetry Eu 3+ coordination compounds [44]. Additionally, the emission peak centered at 615 nm is the strongest one, which results in a red emission with the colorimetric coordinates (0.627, 0.342).…”
Section: Resultsmentioning
confidence: 72%
“…The 4f-4f intensity theory is widely used for lanthanide complexes. [39][40][41][42] The calculation of the intensity parameters was performed for LaOF:Eu 3+ in rhombohedral and tetragonal phases in order to compare the effects of point symmetry on Judd-Ofelt intensity parameters and the correlation with polarizability. The coordination polyhedron and spherical polar coordinates were obtained from crystallographic information 24,25 and the polar spherical coordinates for LaOF:Eu 3+ in rhombohedral and tetragonal phase are shown in Tables S1 and S2, respectively, in the ESI †.…”
Section: Resultsmentioning
confidence: 99%